1991
DOI: 10.1007/bf00436035
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the hedonic and utilitarian sources of consumer attitudes

Abstract: It has been suggested theoretically that consumer attitudes have distinct hedonic and utilitarian components, and that product categories differ in the extent to which their overall attitudes are derived from these two components. This paper reports three studies that validate measurement scales for these constructs and, using them, show that these two attitude dimensions do seem to exist; are based on different types of product attributes; and are differentially salient across different consumer products and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
1,063
2
41

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,623 publications
(1,188 citation statements)
references
References 8 publications
29
1,063
2
41
Order By: Relevance
“…If consumers feel that the message appeals to their sense of practicality and that the object being advertised is going to help them accomplish some objective, the advertising message is said to possess utilitarian value. If, however, consumers feel that the message appeals to their desire for pleasure or suggests that they will experience satisfaction after consuming the advertised object, then the advertising message is said to possess hedonic value (Batra & Ahtola, 1990;Voss et al, 2003).…”
Section: Utilitarian and Hedonic Valuementioning
confidence: 99%
“…If consumers feel that the message appeals to their sense of practicality and that the object being advertised is going to help them accomplish some objective, the advertising message is said to possess utilitarian value. If, however, consumers feel that the message appeals to their desire for pleasure or suggests that they will experience satisfaction after consuming the advertised object, then the advertising message is said to possess hedonic value (Batra & Ahtola, 1990;Voss et al, 2003).…”
Section: Utilitarian and Hedonic Valuementioning
confidence: 99%
“…The utilitarian and hedonic values have been the focus of much interest and research Batra and Ahtola, 1991 ;Babin et al , 1994 ;Wang et al , 2000 ;Millan and Howard, 2007 ;Teller et al , 2008 ). Consumer values have been broadly termed as utilitarian ( Bloch and Bruce, 1984 ;Batra and Ahtola, 1991;Engel et al , 1993 ;Babin et al , 1994 ) which are more task oriented in nature and hedonic which are related to entertainment and fun-seeking behaviour ( Bellenger et al , 1976 ). Bloch and Richins (1983) postulate that hedonic values are characterized by heightened arousal, excitement, adventure and entertainment.…”
Section: Literature Review Hedonic and Utilitarian Shopping Valuesmentioning
confidence: 99%
“…Numerous studies on the measurement of attitudes have shown that attitudes often have two separate components: one interpreted as a cognitive component-sometimes called "utilitarian" or "instrumental"-and the second as an affective component-sometimes called "hedonic" or "consummatory" (e.g., Batra and Athola 1990;Breckler and Wiggins 1989). These studies, however, do not specify the processes through which inputs underlying the affective component enter overall evaluation judgments (i.e., spontaneous associations vs. conscious inferential processes).…”
Section: Feeling-based Evaluationmentioning
confidence: 99%